Flow boiling pressure drop and flow patterns of R-600a in a multiport minichannels ✰ - da Silva, Priscila Forgiarini; de Oliveira, Jeferson Diehl; Copetti, Jacqueline Biancon; Macagnan, Mario Henrique; Cardoso, Elaine Maria [UNESP] (Elsevier, 2023)
This study experimentally investigated the flow boiling pressure drop and flow patterns of R-600a in a horizontal multiport extruded tube with 1.47 mm ID. The experiments were carried out with mass flux between 35 and 165 kgm−2s−1 and heat flux ranging from 4.5 to 18.5 kWm−2 at a saturation temperature of 24 °C. Flow patterns and void fraction distribution amongst channels were observed with a high-speed camera in a visualization section. The influence of mass flux and vapour quality on pressure drop was verified. The flow patterns identified during tests were plug, slug churn and wavy-annular, differently distributed along the channels. The results were also compared with eight different correlations proposed in the literature. Results indicate the dependence of pressure drop on both mass and heat fluxes.
Perte de charge d'ébullition et schémas d'écoulement du R-600a dans un minicanal multiport
Keywords: Flow boiling; Flow patterns; Isobutane; Multiport minichannel; Pressure drop